(untitled) (Communications in Mathematical Research, 2021)
In this paper, an unbounded condition is presented, under which we are able to utilize the interior point homotopy method to solve the Brouwer fixed point problem on unbounded sets. Two numerical examples in R^3 are presented to illustrate the results in this paper.